Impact of ridge cracking on the morphology of buckle-delamination. (November 2020) - Li, Shichen; Yu, Senjiang; Zhang, Jiahui; He, Linghui; Ni, Yong
Abstract: Ridge-cracked blisters form when ridge cracking occurs in a biaxially compressed film on a relatively rigid substrate during buckle-delamination. The observation of telephone-cord (TC) blister with wavy ridge crack indicates that the ridge-cracked blister is not straight-sided as it used to be. How ridge cracking influences the profile of buckle-delamination remains unclear. Based on Föppl–von Kármán (FvK) nonlinear plate theory, we derive an improved analytical solution for a better description of the cross-sectional profile of the straight-sided blister with straight-sided ridge crack through considering the effect of hinge position caused by the ridge crack. Following a similar procedure in the case of the straight-sided ridge-cracked blister, an approximate solution of FvK plate in curvilinear coordinates is further obtained for the cross-sectional profile of the TC ridge-cracked blister. The results show that the position of the ridge crack significantly modifies the asymmetry, the shape, and the maximum deflection of the cross-sectional profile of the resulting blister. Highlights: Nonlinear solutions for the morphology of straigh-sided ridg-cracked blisters and TC-like ridge-cracked blisters are obtained. The presence of ridge crack drastically influences the morphology of straight-sided ridge-cracked blisters and TC-like ridge-cracked blisters. The asymmetry of the cross-sectional profile of the TC-like ridge-cracked blister is mainly determined by the deviation of the position of the ridge crack and the asymmetry enhanced by the amplitude of the compressive stress is suppressed.